2021
DOI: 10.1021/acsmaterialsau.1c00016
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Morphological Properties of Wool Keratin and Cellulose Biocomposites Fabricated Using Ionic Liquids

Abstract: In this study, the structural, thermal, and morphological properties of biocomposite films composed of wool keratin mixed with cellulose and regenerated with ionic liquids and various coagulation agents were characterized and explored. These blended films exhibit different physical and thermal properties based on the polymer ratio and coagulation agent type in the fabrication process. Thus, understanding their structure and molecular interaction will enable an understanding of how the crystallinity of cellulos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…As regards more specifically SAXS spectra, apart from the aforementioned higher degree of lateral aggregation for feather keratin, no significant changes in the broadness of peaks are observed between the two sources. This is promising for the production of composite films with other polymers (e.g., cellulose), where the structural variability these changes may imply do represent an issue [ 43 ]. As the result, a single model has been hypothesized as sufficiently representative for both keratins.…”
Section: Resultsmentioning
confidence: 99%
“…As regards more specifically SAXS spectra, apart from the aforementioned higher degree of lateral aggregation for feather keratin, no significant changes in the broadness of peaks are observed between the two sources. This is promising for the production of composite films with other polymers (e.g., cellulose), where the structural variability these changes may imply do represent an issue [ 43 ]. As the result, a single model has been hypothesized as sufficiently representative for both keratins.…”
Section: Resultsmentioning
confidence: 99%
“…The samples were decomposed between 160 °C and 360 °C, with a slow degradation, divided into steps, thus indicating physical interactions, and no chemical interactions, between the biopolymers (the thermal degradation of cellulose and chitin correspond to 335 °C (ref. 40) and 253 °C, 41 respectively). The starting decomposition at 160 °C can be related to glycerol evaporation (boiling temperature = 182 °C).…”
Section: Resultsmentioning
confidence: 96%
“…Conversely, biocomposite films containing these same components, KER/GCC, show an increase in melting temperature ( Table 3 ), which is possibly due to the combination of two phenomena: mutual macromolecular interaction of the starting components ( Figure S4, Supplementary Materials ) and increased heat capacity when GCC is present, resulting in heating delay due to thermal absorption, i.e., an effect of the amount of thermal energy required to raise the temperature and so dependent on the rate of heating ( Figure S5, Supplementary Materials ). A higher melting temperature of the combination CELL/PCL/KER versus both PCL alone and in the CELL/PCL blend is mostly influenced by the presence of cellulose, while the secondary structures within the keratin contribute to the amorphous regions [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, biocomposite films containing these same components, KER/GCC, show an increase in melting temperature (Table 3), which is possibly due to the combination of two phenomena: mutual macromolecular interaction of the starting components (Figure S4, Supplementary Materials) and increased heat capacity when GCC is present, resulting in heating delay due to thermal absorption, i.e., an effect of the amount of thermal energy required to raise the temperature and so dependent on the rate of heating (Figure S5, Supplementary Materials). A higher melting temperature of the combination CELL/PCL/KER versus both PCL alone and in the CELL/PCL blend is mostly influenced by the presence of cellulose, while the secondary structures within the keratin contribute to the amorphous regions [27]. The following presented results revealed that the studied biocomposite films have different fine structures, which, together with the different miscibility of the three biopolymers and their inter-and intramolecular interactions, represent essential factors affecting the film mechanical properties, such as tensile strength, modulus of elasticity, and breaking strain, which are presented in Table 4 and Figure 11.…”
Section: Atr-ftir Spectroscopy Of Biocomposite Filmsmentioning
confidence: 99%